1999
DOI: 10.1507/endocrj.46.269
|View full text |Cite
|
Sign up to set email alerts
|

Osmoregulation of Vasopressin Secretion in Patients with the Syndrome of Inappropriate Antidiuresis Associated with Central Nervous System Disorders.

Abstract: Abstract.To clarify the characteristics of vasopressin (AVP) secretion in patients with the syndrome of inappropriate antidiuresis (SIAD) related to central nervous system disorders, we examined the response of AVP secretion to osmotic stimulus by hypertonic saline infusion and analyzed the possible causative factors in six patients with SIAD associated with head trauma or cerebral infarction. Hyponatremia developed after head trauma in four patients and cerebral infarction in two patients.In all patients the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 30 publications
1
21
0
Order By: Relevance
“…Kamoi et al 8 observed this syndrome in patients with CNS disorders: subdural hematomas, closed head injury, epilepsy and ischemic cerebrovascular accident. Patients with SIADH and CNS disorders may present persistent AVP secretion with loss of hypotonic suppression, indicating that a careful assessment is required to determine the relationship between persistent AVP secretion and the pathogenesis of hyponatremic disorders 8 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Kamoi et al 8 observed this syndrome in patients with CNS disorders: subdural hematomas, closed head injury, epilepsy and ischemic cerebrovascular accident. Patients with SIADH and CNS disorders may present persistent AVP secretion with loss of hypotonic suppression, indicating that a careful assessment is required to determine the relationship between persistent AVP secretion and the pathogenesis of hyponatremic disorders 8 .…”
Section: Discussionmentioning
confidence: 98%
“…However, these disorders still need to be clarified 8,9 . Currently, no consensus has been found in the literature regarding the behavior of AVP in patients with SBL and in those with brain death.…”
mentioning
confidence: 99%
“…Changes in blood volume were determined from the changes in hematocrit using the formula BV2/BV1=Hct1/ Hct2, assuming no changes in circulating erythrocyte volume. 30 …”
Section: Clinical and Biochemical Assessmentmentioning
confidence: 99%
“…She received hysterectomy for myoma uteri at the age of 40 years in Yukiguni-Yamato General Hospital. At the time, she was diagnosed as primary polydipsia with bilateral non-obstructive hydronephrosis as shown by drip infusion pyerography, since she had normal level of plasma AVP concentration (0.6 pg/ml) as measured by the RIA method previously reported [12][13] although she had polyuria (5000-7000 ml/day) and polydipsia (5000-7000 ml/ day). Before admission, she received Ca ++ antagonist for hypertension.…”
Section: Case Report and Methodsmentioning
confidence: 95%